Study of the Host in Offering Philoxenia in Batik Village Pekalongan City - Noor - Suroija; Karnowahadi - Karnowahadi; Budi - Prasetya; Dody - Setyadi; Yusmar Ardi Hidayat (Admisi dan Bisnis, 2022)
The research objective is to explore the local host's preparedness and capacity in delivering philoxenia experience in which guest travelers experiencing hospitality friendlines and generousity as emotional and social relationship. The population was all SME owners and staff. The number of respondents were 79 people, the sampling technique was purposive convenient non random sampling. The data was analyzed by descriptive and factor analysis. The data shows that general respondents are ready and has high capability in delivering philoxenia experience. One aspect that needs to improve is abilities to maintain good relationship after sales service. There are four variables: physical facilities, location, campoong atmosphere and interpersonal relationship. Location has the lowest mean score. This was fue to the access to these sites and the infrastructure management was not well managed. The highest mean score was interpersonal relationship and has high potential to attract customers. Factor analysis shows that there are 11 indicators of a combined main and supportive factors. Campoong atmosphere factors creates some good conditions like feeling safe and confortable to interact among the people. They are able to build good warm and friendly communication. It is recommended that local host capability in delivering philoxenia should be maintained and improved.